Continuities and discontinuities: changing patterns in journalism and media in Central and Eastern Europe - Stępińska, Agnieszka; Szabó, Gabriella (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2016)
The aim of this Special Issue of Central European Political Studies is to bring media scholars together and to reflect on the current trends in political journalism in our region. The focus of the articles is trained on the discovery of the shifts and continuities in journalistic practises 25 years after the collapse of the communist regimes. Some of the findings and conclusions presented in the volume come from studies conducted within the framework of international comparative research projects such as Worlds of Journalism, Journalistic Role Performance Around the Globe, or Media Accountability and Transparency in Europe (MediaAcT). The others come from single, national empirical studies or analyses on the media systems conducted in the Central and Eastern countries.